EFFECTS OF A PSYCHOMOTOR TRAINING ON LOCOMOTOR SKILLS AMONG CHILDREN (International Journal of Food and Nutritional Sciences, 2022)
This study aimed to investigate the effects of a 12-week psychomotor training intervention on locomotor skills among young children. Forty schoolgirls aged 6 to 7 years from Tiruchendur Taluk, Tamil Nadu, were randomly assigned to either an intervention group (n=20) or a control group (n=20). The intervention group participated in three training sessions per week, focusing on activities designed to enhance walking and skipping skills. Pre-test and post-test assessments of locomotor skills were conducted using the MOBAK test Edison 2. Paired sample t-tests were used to analyze pre-test and post-test scores within each group, while analysis of covariance (ANCOVA) was employed to compare post-test scores between the intervention and control groups, controlling for potential covariates. Results indicated significant improvements in walking and skipping abilities among participants in the intervention group (p < 0.05). Conversely, no significant changes were observed in the control group. The ANCOVA analysis further supported the intervention's efficacy, revealing significant differences in post-test scores between the two groups (p < 0.05). These findings provide compelling evidence for the effectiveness of psychomotor training interventions in enhancing locomotor skills among young children, highlighting the importance of structured training programs in promoting motor skill development during early childhood.